{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Fall 2007 - Hohnhold's Class - Exam 2 (Version B)

# Fall 2007 - Hohnhold's Class - Exam 2 (Version B) - Midterm...

This preview shows pages 1–3. Sign up to view the full content.

Midterm 2 for Math 20B. Fall Quarter 2007, UCSD Henning Hohnhold Name: Section: #1: #2: #3: #4: Total: (1) Sequences and Series. (a) (5 points) Explain briefly which of the following two sequences are convergent. If a sequence converges, find its limit. ( i ) a n = 7( n 3 + 5) (4 n 2 + 1)( n + 1) ( ii ) a n = ( - 1) n 7( n 3 + 5) (4 n 2 + 1)( n + 1) We have lim n →∞ 7( n 3 + 5) (4 n 2 + 1)( n + 1) = lim n →∞ 7 n 3 + 35 4 n 3 + 4 n 2 + n + 1 = lim n →∞ n 3 (7 - 35 /n 3 ) n 3 (4 + 4 /n + 1 /n 2 + 1 /n 3 ) = 7 4 The sequence in (ii) diverges, since for large n its values jump back and forth between numbers close to 7 4 and close to - 7 4 . (b) (5 points) Determine whether the following series are convergent. If so, find their value. ( i ) 7 + 7 4 + 7 16 + 7 64 + 7 256 + ... ( ii ) 1 2 + 3 4 + 9 8 + 27 16 + 81 32 + ... The second series is the geometric series 1 2 n =0 ( 3 2 ) n ; it diverges because 3 2 > 1. The first series is a convergent geometric series: 7 + 7 4 + 7 16 + 7 64 + 7 256 + ... = 7 X n =0 1 4 n = 7 1 1 - 1 4 = 28 3

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
(2) Partial fraction decompositions. (a) (9 points) Use the method of partial fractions to find the indefinite integral of the rational function g ( x ) = - x 2 - 3 x + 18 x 3 + x 2 + 9 x + 9 . Hint: x 3 + x 2 + 9 x + 9 = ( x + 1)( x 2 + 9) . Using the hint, we set up the PFD as - x 2 - 3 x + 18 x 3 + x 2 + 9 x + 9 = A x + 1 + Bx + C x 2 + 9 . This is equivalent to - x 2 - 3 x + 18 = A ( x 2 + 9) + ( Bx + C )( x + 1). Choosing x = - 1 this gives - 1 + 3 + 18 = 10 A , so A = 2. Multiplying out, we see - x 2 - 3 x + 18 = ( A + B ) x 2 + ( C + B ) x + 9 A + C so that B = - 1 - A = - 3 and C = - 9 A + 18 = 0. Finally, we integrate: Z g ( x ) dx = Z 2 x + 1 - 3 x x 2 + 9 dx = 2 ln( x + 1) - 3 2 ln( x 2 + 9) + C, where we used the substitution rule to integrate the second term. (b) (4 points) Find the indefinite integral of f ( x ) = - 2 x 3 - 3 x 2 - 21 x x 3 + x 2 + 9 x + 9 . Hint: Use long division and your result from part (a). Long division gives (after only one step): f ( x ) = - 2 x 3 - 3 x 2 - 21 x x 3 + x 2 + 9 x + 9 = - 2 + - x 2 - 3 x + 18 x 3 + x 2 + 9 x + 9 = 1 + g ( x ) So we can use (a) to compute the indefinite integral of f ( x ): Z f ( x ) dx = Z 1 + g ( x ) dx = - 2 x + 2 ln( x + 1) - 3 2 ln( x 2 + 9) + C.
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}